Using digital game-based learning to foster multimodal literacy in left-behind children of migrant workers: possibilities and challenges - Shen, Yanan; Ab Jalil, Habibah; Jamaluddin, Rahimah (Transnational Press London, 2023)
Digital games offer opportunities for the youths development of multimodal literacy required in the technology-driven world. However, both digital games and multimodal literacy are undervalued in rural contexts characterized by migrant parents and leftbehind children. This qualitative case study conceptualized systematic guidance to foster students multimodal literacy through digital games and trialled its possibilities and challenges in enhancing left-behind children of migrant workers in a suburban school. Sixteen student participants engaged in critical game analysis and game video design in a 16-session classroom-based program, with the guidance of the researchers and two local teachers. Multiple data-collection methods were applied to capture students learning progress aligned with the teachers perceptions. Thematic analysis and multimodal analysis were utilized to process data. The findings indicate that this instructional approach deepened and broadened the students critical viewing and application of multimodal texts and enhanced their proficiency in leveraging digital tools for multimodal communication. The challenges include students varied competencies and motivation, time constraints, and limited access to digital devices. We advocate for integrating DGBL in literacy classrooms, thus catering to left-home students demands and social needs in the digital age. Meanwhile, joint efforts are necessitated to address perennial challenges in this education reform and inequities within the process.